Helpful or harmful? The impact of the ketogenic diet on eating disorder outcomes in type 1 diabetes mellitus. Issue 4 (4th July 2022) - Schneider, Suzanne; Biggerstaff, Deborah L; Barber, Thomas M
ABSTRACT: Introduction: Eating disorders (EDs) are common complications in people with type 1 diabetes (PwT1D), given the rigid focus on food and insulin dose adjustment. Dietary recommendations for T1D match those for the general population, yet many fail to achieve target HbA1c. Evidence suggests that lower carbohydrate meals and thus reduced insulin requirements may decrease inconsistencies in insulin absorption, maintain euglycemia and weight. Dietary restriction is a recognized risk factor for ED development, and Ketogenic Diets (KD) involve restriction of common family-based foods, thus impacting social normality and microbiome diversity. We reviewed the current literature on PwT1D following a KD to understand effects on ED risks. Areas covered: Published data from MEDLINE, Embase, and PsycINFO were used. Search terms included: type 1 diabetes mellitus; or insulin dependent diabetes or T1D AND EDs or anorexia or bulimia or disordered eating AND low-carbohydrate diet or carbohydrate restricted diet or low carb diet or ketogenic diet. Expert opinion: Research into the effects of KDs on ED outcomes in PwT1D are limited, given the concerns over risks of diabetic ketoacidosis, hypoglycemia, and dyslipidemia. Longer term studies on the participants' experience and motivations of adhering or admonishing the diet are needed.